Development of animation-based cooperative learning media on Lampung folk tales to improve learning outcomes in elementary school students - Nursanti, Aprilia; Ariyani, Farida; Perdana, Ryzal; Firmansyah, Hendri (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
This study aimed to develop and examine the feasibility and preliminary effectiveness of an animation-based learning medium integrated with Cooperative Learning for teaching Lampung folk tales in elementary schools. The study was motivated by low student achievement and the limited availability of culturally contextualized digital media in local language instruction. Using a Research and Development (R&D) approach, the learning media was developed through the ADDIE model, encompassing Analysis, Design, Development, Implementation, and Evaluation. The participants consisted of 25 fourth-grade students from SDN 3 Rajabasa, Bandar Lampung. Expert validation indicated a high level of feasibility, with an average score of 88%. Learning outcomes were examined using a one-group pretest–posttest design, revealing a substantial increase in students' scores from a mean of 48.4 to 93.2. Paired-sample t-test results showed a statistically significant improvement (p < 0.001), accompanied by a large effect size (Cohen's d = 3.40), suggesting a strong learning impact within the study context. Students also reported very positive responses to the learning experience, with an average satisfaction score of 4.9 out of 5. These findings indicate that animation-based cooperative learning media can effectively support student engagement, comprehension, and appreciation of Lampung cultural values. While the results are promising, they should be interpreted as preliminary due to the limited sample and research design. The study offers practical insights for developing culturally responsive digital learning resources aligned with Indonesia's Merdeka Belajar (Freedom to Learn) policy.